Ionic membrane based on functional composition regulation and preparation method thereof
By using the composite regulation of polystyrene and polyethylene, an ordered ion conduction channel was constructed, which solved the problems of high cost and poor mechanical properties of existing ion exchange membranes, and realized the preparation of low-cost, high-performance ion exchange membranes, thereby improving battery performance.
Patent Information
- Application Number
- CN202510890104.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-30
- Publication Date
- 2025-10-28
AI Technical Summary
Existing ion-exchange membrane materials are expensive and have poor mechanical properties, making them difficult to widely apply in fields such as fuel cells, flow batteries, and water electrolysis.
By compounding polystyrene and polyethylene, regulating their ratio and degree of sulfonation, constructing ordered ion conduction channels, forming hydrophobic and hydrophilic microstructures, and combining the rigidity of polystyrene and the flexibility of polyethylene, low-cost, high-performance ion membranes are prepared.
While reducing costs, the mechanical properties and ion conductivity of the ion membrane are improved, a continuous ion transmission channel is formed, and battery performance is improved.
Smart Images

Figure BDA0005474727160000101 
Figure BDA0005474727160000111
Abstract
Description
Technical Field
[0001] This invention relates to the field of ion-exchange membrane chemistry, and the products are applied in fuel cells, flow batteries, water electrolysis, and the chlor-alkali industry. This invention relates to the preparation of ion-exchange membrane materials, constructing ordered ion conduction channels through optimized control of the ion-exchange membrane microstructure, specifically an ion-exchange membrane based on functional composition control and its preparation method. Background Technology
[0002] The primary function of ion-exchange membranes is to transport ions through ordered channels formed by adjusting their polymer microstructure, thus creating a closed loop with the battery. Furthermore, ion-exchange membranes must possess good mechanical strength and stability. Currently, perfluorosulfonic acid membranes are mainly used in fuel cells, flow batteries, and water electrolysis. While perfluorosulfonic acid membranes exhibit excellent battery performance, their high cost hinders their further development in energy devices.
[0003] Patent CN114573934B relates to a composite of modified polystyrene and sulfonated polymers such as perfluorosulfonate resin or sulfonated polyarylene ethers. This composite utilizes a combination of multiple components to construct a microscopic hydrogen bond network and complexation, which can improve ion conductivity and increase stability during use through complexation. However, the composite of modified polystyrene and perfluorosulfonate resin still uses expensive perfluorosulfonate resin. Furthermore, the rigid structure of the benzene ring in polystyrene itself results in poor mechanical properties of the ion exchange membrane. The composite of modified polystyrene with sulfonated polyarylene ethers and other polymers also suffers from poor membrane mechanical properties due to the aromatic structure of these polymers, failing to improve the mechanical properties of the ion exchange membrane.
[0004] Compared with patent CN114573934B, this invention uses polyethylene to prepare ion exchange membranes, which avoids the use of expensive perfluorosulfonic acid resin and reduces costs. On the other hand, the use of flexible polyethylene segments ensures the flexibility of the composite membrane, resulting in good mechanical properties of the prepared composite ion conductor.
[0005] Patent CN118344510A relates to the preparation of sulfonated polystyrene, which combines the mechanical properties of polystyrene with the flexibility of the alkyl chain by introducing flexible alkyl chains and sulfonic acid groups onto polystyrene, and utilizes the sulfonic acid groups to regulate ion conduction channels.
[0006] Compared to patent CN118344510A, this invention uses longer polyethylene molecules to composite with polystyrene, instead of covalently attaching very short alkyl chains to polystyrene. On one hand, the longer polyethylene molecules used in this invention provide better flexibility to the polymer chain segments; on the other hand, the method of blending polyethylene molecules is simpler than the method of covalent bonding. Summary of the Invention
[0007] To reduce costs and further control the mechanical properties and ionic conductivity of ion exchange membranes, this invention provides an ion exchange membrane with reduced perfluorosulfonic acid content and its preparation method.
[0008] This invention utilizes the mechanical strength of the benzene ring in polystyrene combined with the flexibility of polyethylene to prepare an ion-exchange membrane using a polystyrene-polyethylene composite. Selective sulfonation is then applied, and by controlling the ratio of polystyrene to polyethylene and the degree of sulfonation, the microstructure of the ion-exchange membrane can be modulated, further constructing an ordered ion conduction channel. Simultaneously, through design and control, the degree and ratio of sulfonation can be further designed and adjusted to achieve the design and control of the functional components of the ion-exchange membrane, thereby maximizing the role of each functional component and regulating the mechanical properties and ionic conductivity of the membrane.
[0009] Microscopically, polystyrene and polyethylene are both hydrophobic components, while sulfonic acid groups are hydrophilic components. During the preparation of the ion-exchange membrane, the hydrophilic and hydrophobic components aggregate and assemble into their respective microscopic phase structures due to their differences in hydrophilic and hydrophobic properties. Adjusting the ratio of polystyrene to polyethylene can adjust the ratio of the mechanical support component and the flexible chain segment component of the ion-exchange membrane, thereby adjusting the rigidity and flexibility of the formed microscopic hydrophobic structure. Adjusting the degree of sulfonation can adjust the proportion of sulfonate groups, thereby adjusting the formed microscopic hydrophilic structure. The hydrophobic structure formed by polystyrene and polyethylene and the hydrophilic structure formed by sulfonate groups, due to their differences in hydrophilic and hydrophobic properties, form a unique hydrophilic-hydrophobic microstructure. In the dry membrane state, the hydrophilic structure formed by sulfonate groups is approximately spherical and uniformly distributed within the hydrophobic structure formed by polystyrene and polyethylene. When the ion-exchange membrane is operating in the battery, water molecules enter the membrane, the sulfonate groups absorb water and swell, and the spherical hydrophilic structures formed by the sulfonate groups gradually expand and interconnect. Adjusting the degree of sulfonation, and thus the size and proportion of the resulting hydrophilic microstructures, can regulate the continuity and order of ion conduction channels after the hydrophilic structure absorbs water and swells. Similarly, controlling the ratio of polystyrene to polyethylene, and adjusting the rigidity and flexibility of the resulting hydrophobic microstructures, can regulate the compression and swelling of the hydrophilic structure.
[0010] Macroscopically, polystyrene serves as the mechanical support component of the ion-exchange membrane, while polyethylene serves as the flexible segment component. Adjusting the ratio of polystyrene to polyethylene can adjust the ratio of the mechanical support component and the flexible segment component in the ion-exchange membrane. Increasing the proportion of polystyrene increases the overall mechanical strength of the ion-exchange membrane, but reduces its toughness due to the reduced proportion of polyethylene, which provides flexibility. Conversely, decreasing the proportion of polystyrene decreases the mechanical strength of the ion-exchange membrane, but increases its toughness. Both polystyrene and polyethylene are non-conductive components. Sulfonation treatment of both, introducing sulfonic acid groups, can improve the conductivity of the ion-exchange membrane. The higher the degree of sulfonation, the more sulfonic acid groups are introduced, and the higher the conductivity of the ion-exchange membrane. However, sulfonic acid groups are hydrophilic groups; when the ion-exchange membrane is immersed in water, the sulfonic acid groups absorb water and swell. The more sulfonic acid groups there are, the greater the water absorption, and the greater the decrease in the mechanical properties of the membrane. Therefore, the degree of sulfonation needs to be controlled, i.e., introducing a relatively large number of sulfonic acid groups to increase conductivity without excessively reducing mechanical properties due to excessive water absorption.
[0011] In summary, at the microscopic level, adjusting the ratio of polystyrene to polyethylene modulates the rigidity and flexibility of the resulting hydrophobic microstructure. Adjusting the degree of sulfonation alters the size and proportion of the resulting hydrophilic microstructure, thereby modifying the hydrophilic / hydrophobic microstructure of the ion-exchange membrane and the orderliness of the ion conduction channels. At the macroscopic level, controlling the ratio of polystyrene to polyethylene regulates the mechanical properties of the ion-exchange membrane, and controlling the degree of sulfonation regulates its conductivity, as well as its mechanical properties under hydration conditions.
[0012] The above-mentioned objective of this invention is achieved through the following technical solution:
[0013] An ion exchange membrane based on functional composition regulation, wherein the mass fraction of sulfonated polystyrene in the ion exchange membrane is x, the mass fraction of sulfonated polyethylene is y, x+y=100%, and the thickness of the ion exchange membrane is 20~300μm.
[0014] A method for preparing an ion-exchange membrane based on functional composition regulation includes the following steps:
[0015] (1) The average molecular weight of polystyrene is 3,000 to 13,000,000 Da;
[0016] (2) Sulfonation of polystyrene, the method is as follows:
[0017] Polystyrene is poured into a three-necked flask and pre-sulfonated with sulfuric acid at a concentration of 0.01-5 g / mL, and stirred at 60-120°C for 0.5-5 hours. Then, chlorosulfonic acid is added for further sulfonation, and the mixture is stirred at 60-120°C for 1-48 hours, maintaining a concentration of 0.01-5 g / mL. After the reaction is complete, the flask is cooled to room temperature, and the solution is slowly added dropwise to cold water. The mixture is then rinsed with cold pure water until neutral. By controlling the reaction time, the degree of sulfonation of polystyrene can be achieved from 0-300%.
[0018] (3) Sulfonation of polyethylene can begin from the start of synthesis, as follows:
[0019] An organic solution of ethylene is added to a flask. The organic solvent can be one or more solvents such as ethanol, benzene, diethyl ether, and carbon tetrachloride. An organic solution of vinyl sulfonic acid is also added to the flask. The organic solvent can include ethanol, benzene, diethyl ether, and carbon tetrachloride. An initiator is then added to the flask. The initiator can be one or more of hydrogen peroxide, azobisisobutyronitrile, benzoyl peroxide, and potassium perchlorate. The molar ratio of initiator to ethylene and vinyl sulfonic acid is controlled between 1:50 and 1:3000. The reaction is stirred at 30-120°C for 0.5-24 hours. After the reaction is complete, the mixture is cooled to room temperature, and the flask is quenched with liquid nitrogen to eliminate free radicals. The mixture is then washed with water to obtain the product. By controlling the ratio of initiator to monomer and the reaction time, the molecular weight of polyethylene can be controlled. Simultaneously, the degree of sulfonation is controlled by controlling the ratio of ethylene to vinyl sulfonic acid. The degree of sulfonation of polyethylene ranges from 0-100%.
[0020] (4) After mixing sulfonated polystyrene, sulfonated polyethylene and organic solvent, filter to obtain casting solution; form the casting solution into a membrane to obtain the ion membrane.
[0021] The mixing process includes sequential ultrasonication and stirring; the ultrasonication time is 30–40 min; and the stirring time is 24–48 h.
[0022] The film formation process includes: adding the casting liquid droplets onto the substrate surface and then sequentially drying and annealing.
[0023] The drying temperature is 60–100°C and the time is 24–48 h; the annealing temperature is 120–200°C and the time is 2–10 h.
[0024] The organic solvent preferably includes one or more of N,N-dimethylformamide, N,N-dimethylacetamide, N-methyl-2-pyrrolidone, dimethyl sulfoxide, toluene, trichloroethane, and dichloroethane.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] The ion-exchange membrane of this invention is composed of sulfonated polystyrene and sulfonated polyethylene. Perfluorosulfonic acid membranes have the advantages of good proton conductivity and stability, but are very expensive. The ion-exchange membrane of this invention, by combining polystyrene and polyethylene, possesses both a rigid structure and flexible segments. Furthermore, sulfonation allows for the control of the ion transport channel size, effectively increasing proton conductivity and the barrier effect on active materials, thus replacing perfluorosulfonic acid membranes and reducing the cost of ion exchange membranes. The sulfonic acid groups in the sulfonated polystyrene and polyethylene aggregate to form ion clusters, promoting ion transport. The dense, rigid framework of polystyrene effectively prevents the permeation of active materials, significantly impacting battery performance. Simultaneously, the low cost of sulfonated polystyrene and sulfonated polyethylene allows for better control of the overall battery cost.
[0027] Simultaneously, by adjusting the degree of sulfonation of polystyrene and polyethylene, as well as their compounding ratio, a series of polystyrene combinations with varying degrees of sulfonation can be obtained. By adjusting the ratio between polystyrene with rigid benzene rings and polyethylene with flexible segments, the microstructure of the polymer can be controlled. Through design and regulation, the function of polystyrene in providing mechanical strength and the function of polyethylene's flexible segments in providing toughness can be utilized. Furthermore, through appropriate sulfonation, hydrophilic groups are introduced onto the functional polystyrene and polyethylene, forming continuous ion transport channels in the hydrated state. Moreover, by controlling the degree of sulfonation and thus the structure of the ion transport channels on the microstructure of the ion exchange membrane, the design and control of the functional components of the ion exchange membrane can be achieved, thereby maximizing the role of each functional component and regulating the mechanical properties and ionic conductivity of the ion exchange membrane. Detailed Implementation
[0028] The present invention will be further illustrated below with reference to specific embodiments. It is worth noting that these embodiments are for illustrative purposes only and do not limit the scope of application of the present invention.
[0029] Example 1
[0030] Sulfonated polystyrene (SPS) (weight average molecular weight 100,000 Da, sulfonation degree 50%) was added to DMF and dissolved completely in an oven at 60°C for 12 hours, followed by stirring at room temperature for 24 hours to obtain a casting solution with a sulfonated polystyrene (SPS) solid content of 10%. Sulfonated polyethylene (SPE) (weight average molecular weight 80,000 Da, sulfonation degree 50%) was added to DMF and dissolved completely in an oven at 60°C for 12 hours, followed by stirring at room temperature for 24 hours to obtain a casting solution with a sulfonated polyethylene (SPE) solid content of 10%. SPS casting solution and SPE casting solution were mixed together in a 1:1 ratio. The resulting casting solution was used to prepare a film by solution casting. The wet film was placed on a glass plate in a drying oven for drying. The solvent was evaporated at 80°C for 12 hours. After cooling to room temperature, the film was peeled off from the glass plate and then placed in a nitrogen-filled oven for annealing at 120°C for 6 hours to obtain an ion exchange membrane SE55-1-1 with a thickness of 100 μm.
[0031] Example 2
[0032] Sulfonated polystyrene (SPS) (weight average molecular weight 100,000 Da, sulfonation degree 50%) was added to DMF and dissolved completely in an oven at 60°C for 12 hours, followed by stirring at room temperature for 24 hours to obtain a casting solution with a sulfonated polystyrene (SPS) solid content of 10%. Sulfonated polyethylene (SPE) (weight average molecular weight 80,000 Da, sulfonation degree 50%) was added to DMF and dissolved completely in an oven at 60°C for 12 hours, followed by stirring at room temperature for 24 hours to obtain a casting solution with a sulfonated polyethylene (SPE) solid content of 10%. SPS casting solution and SPE casting solution were mixed together in a 1:2 ratio. The resulting casting solution was used to prepare a film by solution casting. The wet film was placed on a glass plate in a drying oven for drying. The solvent was evaporated at 80°C for 12 hours. After cooling to room temperature, the film was peeled off from the glass plate and placed in a nitrogen-filled oven for annealing at 120°C for 6 hours to obtain an ion exchange membrane SE55-1-2 with a thickness of 100 μm.
[0033] Example 3
[0034] Sulfonated polystyrene (SPS) (weight average molecular weight 100,000 Da, sulfonation degree 30%) was added to DMF and dissolved completely in an oven at 60°C for 12 hours, followed by stirring at room temperature for 24 hours to obtain a casting solution with a sulfonated polystyrene (SPS) solid content of 10%. Sulfonated polyethylene (SPE) (weight average molecular weight 80,000 Da, sulfonation degree 50%) was added to DMF and dissolved completely in an oven at 60°C for 12 hours, followed by stirring at room temperature for 24 hours to obtain a casting solution with a sulfonated polyethylene (SPE) solid content of 10%. SPS casting solution and SPE casting solution were mixed together in a 1:1 ratio. The resulting casting solution was used to prepare a membrane by solution casting. The wet membrane was placed on a glass plate in a drying oven for drying. The solvent was evaporated at 80°C for 12 hours. After cooling to room temperature, the membrane was peeled off from the glass plate and then placed in a nitrogen-filled oven for annealing at 120°C for 6 hours to obtain an ion exchange membrane SE35-1-1 with a thickness of 100 μm.
[0035] Example 4
[0036] Sulfonated polystyrene (SPS) (weight average molecular weight 100,000 Da, sulfonation degree 30%) was added to DMF and dissolved completely in an oven at 60°C for 12 hours, followed by stirring at room temperature for 24 hours to obtain a casting solution with a sulfonated polystyrene (SPS) solid content of 10%. Sulfonated polyethylene (SPE) (weight average molecular weight 80,000 Da, sulfonation degree 50%) was added to DMF and dissolved completely in an oven at 60°C for 12 hours, followed by stirring at room temperature for 24 hours to obtain a casting solution with a sulfonated polyethylene (SPE) solid content of 10%. SPS casting solution and SPE casting solution were mixed together in a 1:2 ratio. The resulting casting solution was used to prepare a membrane by solution casting. The wet membrane was placed on a glass plate in a drying oven for drying. The solvent was evaporated at 80°C for 12 hours. After cooling to room temperature, the membrane was peeled off from the glass plate and then placed in a nitrogen-filled oven for annealing at 120°C for 6 hours to obtain an ion exchange membrane SE35-1-2 with a thickness of 100 μm.
[0037] Comparative Example 1
[0038] Polystyrene (PS) (weight average molecular weight 100,000 Da, sulfonation degree 0%) was added to DMF and dissolved completely in an oven at 60℃ for 12 h, followed by stirring at room temperature for 24 h to obtain a casting solution with a polystyrene PS solid content of 10%. Polyethylene (SPE) (weight average molecular weight 80,000 Da, sulfonation degree 0%) was added to DMF and dissolved completely in an oven at 60℃ for 12 h, followed by stirring at room temperature for 24 h to obtain a casting solution with a polyethylene SPE solid content of 10%. The PS casting solution and SPE casting solution were mixed together in a 1:1 ratio, and the resulting casting solution was used to prepare a film by solution casting. The resulting wet film was placed on a glass plate in a drying oven for drying, and the solvent was evaporated at 80℃ for 12 h. After cooling to room temperature, the film was peeled off from the glass plate and annealed in a nitrogen-filled oven at 120℃ for 6 h to obtain an ion exchange membrane SE00-1-1 with a thickness of 100 μm.
[0039] Comparative Example 2
[0040] Polystyrene (PS) (weight average molecular weight 100,000 Da, sulfonation degree 0%) was added to DMF and dissolved completely in an oven at 60°C for 12 hours, followed by stirring at room temperature for 24 hours to obtain a casting solution with a polystyrene PS solid content of 10%. Sulfonated polyethylene (SPE) (weight average molecular weight 80,000 Da, sulfonation degree 50%) was added to DMF and dissolved completely in an oven at 60°C for 12 hours, followed by stirring at room temperature for 24 hours to obtain a casting solution with a sulfonated polyethylene SPE solid content of 10%. PS casting solution and SPE casting solution were mixed together in a 1:1 ratio. The resulting casting solution was used to prepare a film by solution casting. The wet film was placed on a glass plate in a drying oven for drying. The solvent was evaporated at 80°C for 12 hours. After cooling to room temperature, the film was peeled off from the glass plate and placed in a nitrogen-filled oven for annealing at 120°C for 6 hours to obtain an ion exchange membrane SE05-1-1 with a thickness of 100 μm.
[0041] Comparative Example 3
[0042] Sulfonated polystyrene (SPS) (weight average molecular weight 100,000 Da, sulfonation degree 50%) was added to DMF and dissolved completely in an oven at 60°C for 12 hours, followed by stirring at room temperature for 24 hours to obtain a casting solution with a sulfonated polystyrene (SPS) solid content of 10%. Polyethylene (PE) (weight average molecular weight 80,000 Da, sulfonation degree 0%) was added to DMF and dissolved completely in an oven at 60°C for 12 hours, followed by stirring at room temperature for 24 hours to obtain a casting solution with a polyethylene (PE) solid content of 10%. SPS casting solution and PE casting solution were mixed together in a 1:1 ratio. The resulting casting solution was used to prepare a membrane by solution casting. The wet membrane was placed on a glass plate in a drying oven for drying. The solvent was evaporated at 80°C for 12 hours. After cooling to room temperature, the membrane was peeled off from the glass plate and then placed in a nitrogen-filled oven for annealing at 120°C for 6 hours to obtain an ion exchange membrane SE50-1-1 with a thickness of 100 μm.
[0043] Conductivity test:
[0044] The surface resistivity AR (Ωcm) of the membrane sample 2 The impedance was measured using a VersaSTAT3 impedance analyzer from AMETEK (USA) in the frequency range of 0.1 Hz to 10 MHz using the two-probe method, with a perturbation voltage set to 10 mV. The test setup consisted of a diffusion cell with graphite rod electrodes inserted on both sides, each containing 35 mL of 3M H₂SO₄ solution. A membrane sample (3 × 3 cm) was then placed... 2 The membrane was pre-soaked in 3M H₂SO₄ solution for 12 hours and then clamped in the middle of the diffusion cell. The resistances of the test apparatus with and without the membrane are denoted as r₁ and r₂, respectively. AR and the proton conductivity (S / cm) in the membrane permeation direction are also recorded. -1 It is calculated using the following formula:
[0045] AR = (r1 - t2) × S
[0046]
[0047] Where L (cm) is the thickness of the membrane sample, and S (cm) is the thickness of the membrane sample. 2 The effective contact area of the membrane sample with the solution in the middle of the diffusion cell is 2.0 cm². 2 .
[0048] The test results from the examples and comparative examples show that increasing the proportion of polyethylene component, i.e., adding flexible chain segments in the hydrophobic phase region of the ion exchange membrane, reduces the mechanical strength of the membrane. Increasing the degree of sulfonation increases the hydrophilic components within the ion exchange membrane, making it easier to form ordered ion conduction channels, thus increasing the membrane's conductivity. Compared to the comparative examples with no sulfonation and low sulfonation, the conductivity of the ion exchange membranes in the examples is significantly increased. While increasing the degree of sulfonation and introducing sulfonic acid groups improves conductivity, it also increases the water absorption of the ion exchange membrane and reduces its mechanical properties. Comparing the examples and comparative examples, at the same degree of sulfonation, introducing sulfonic acid groups onto polyethylene has a greater impact on the mechanical properties of the ion exchange membrane than introducing them onto polystyrene.
[0049] Therefore, adjusting the ratio of polyethylene to polystyrene can regulate the microscopic hydrophobic phase structure of the ion-exchange membrane and adjust the ratio of rigidity to flexibility. Adjusting the degree of sulfonation can regulate the ratio of sulfonic acid groups, thereby regulating the microscopic hydrophilic phase structure of the ion-exchange membrane. By adjusting the ratio and degree of sulfonation, and optimizing the microscopic hydrophobic and hydrophilic phase structures, an ordered ion conduction channel can be further constructed.
[0050] Table 1. Test results for examples and comparative examples.
[0051]
[0052] It should also be noted that the various specific technical features described in the above embodiments can be combined in any suitable manner without contradiction. To avoid unnecessary repetition, this disclosure will not describe the various possible combinations separately.
Claims
1. An ion-exchange membrane based on functional composition regulation, characterized in that, The mass fraction of sulfonated polystyrene in the ion exchange membrane is x, the mass fraction of sulfonated polyethylene is y, x+y=100%, and the thickness of the ion exchange membrane is 20~300μm.
2. A method for preparing an ion-exchange membrane based on functional composition regulation, characterized in that, Includes the following steps: (1) Select polystyrene with an average molecular weight of 3,000 to 1,300,000 Da; (2) Polystyrene sulfonation; (3) Polyethylene sulfonation; (4) After mixing sulfonated polystyrene, sulfonated polyethylene and organic solvent, filter to obtain casting solution; form the casting solution into a membrane to obtain the ion membrane.
3. The method for preparing an ion-exchange membrane based on functional composition regulation according to claim 2, characterized in that, Step (2) of the polystyrene sulfonation method includes: Polystyrene is pre-sulfonated with sulfuric acid at a concentration of 0.01-5 g / mL and stirred at 60-120°C for 0.5-5 hours. Chlorosulfonic acid is then added for further sulfonation, and the mixture is stirred at 60-120°C for 1-48 hours while maintaining a concentration of 0.01-5 g / mL. After the reaction is complete, the mixture is cooled to room temperature, and the solution is slowly added dropwise to cold water and rinsed with cold pure water until neutral.
4. The method for preparing an ion-exchange membrane based on functional composition regulation according to claim 3, characterized in that, By controlling the reaction time, the degree of sulfonation of polystyrene can range from 0% to 300%.
5. The method for preparing an ion-exchange membrane based on functional composition regulation according to claim 2, characterized in that, Step (3) The method for sulfonating polyethylene includes: Ethylene, vinyl sulfonic acid and organic solvent are mixed, and an initiator is added. The molar ratio of the initiator to ethylene and vinyl sulfonic acid is controlled at 1:50 to 1:3000. The mixture is stirred at 30-120℃ for 0.5-24 hours. After the reaction is completed, the mixture is cooled to room temperature and free radicals are quenched by liquid nitrogen. The mixture is then washed with water to obtain the product.
6. The method for preparing an ion-exchange membrane based on functional composition regulation according to claim 5, characterized in that, By controlling the ratio of initiator to monomer in the reaction and controlling the reaction time, the molecular weight of polyethylene can be controlled; at the same time, the degree of sulfonation can be controlled by controlling the ratio of ethylene to vinyl sulfonic acid, with the degree of sulfonation of polyethylene ranging from 0 to 100%.
7. The method for preparing an ion-exchange membrane based on functional composition regulation according to claim 5, characterized in that, The organic solvent is one or more of ethanol, benzene, diethyl ether, and carbon tetrachloride; the initiator is one or more of hydrogen peroxide, azobisisobutyronitrile, benzoyl peroxide, and potassium perchlorate.
8. The method for preparing an ion-exchange membrane based on functional composition regulation according to claim 2, characterized in that, Step (4) mixing includes sonication and stirring in sequence; the sonication time is 30-40 min; the stirring time is 24-48 h.
9. The method for preparing an ion exchange membrane based on functional composition regulation according to claim 2, step (4) membrane formation includes: After the casting solution is dropped onto the substrate surface, it is dried and annealed in sequence; the drying temperature is 60-100℃ and the time is 24-48h; the annealing temperature is 120-200℃ and the time is 2-10h.
10. The method for preparing an ion-exchange membrane based on functional composition regulation according to claim 2, wherein the organic solvent in step (4) includes one or more of N,N-dimethylformamide, N,N-dimethylacetamide, N-methyl-2-pyrrolidone, dimethyl sulfoxide, toluene, trichloroethane, and dichloroethane.
Citation Information
Patent Citations
Sulfonated polymer / modified polystyrene composite and ion exchange membrane
CN114573934B
Preparation and application of sulfonated polystyrene proton exchange membrane
CN118344510A